Clinical Observation and Performance of High Power Diode Laser in the Treatment of Oral Lesions - Seeron, Maral I.; Ismail, Ayad M.; Hajim, Khalil I. (Iraqi Journal of Laser, 2005)
In this work, oral lesions belong to 17 patients, 7 males and 10 females. Their ages range between 15 and 45 years. Follow up was conducted after one day, 7 days, 14 days, one month, and finally 3 months postoperatively. The study lasted for 1.5 year. Surgical diode laser with wavelength of 810 ± 20 nm, with two power levels of 10 and 15 W were used in contact and in non-contact mode via optical fiber. The postoperative outcome revealed; greater haemostatic capability, dry, sealed wound and noticeable lack in pain sensation